Dukungan Pemerintah dalam Program Bersama Lindungi Anak (BERLIAN) untuk Mencegah Kekerasan pada Anak di Kota Bukittinggi - Rizky Pratama, Aditya; Sasmita, Siska (Policy, Law and Political Research Center, 2025)
This study aims to analyze government support in implementing the Joint Program to Protect Children (Berlian) and identify obstacles faced in preventing child abuse in Bukittinggi City. The research method used a descriptive qualitative approach with data collection techniques through in-depth interviews. The research informants were determined using a purposive sampling technique of nine people. The results showed that government support in the Diamond Program covered four main aspects: management of organizational resources, development of organizational engagement climate, regulation of work levels, and optimization of employee engagement. The constraints faced by implementing this program include a limited budget and human resources. This research contributes to understanding the effectiveness of child protection programs at the local government level.